2010
DOI: 10.1007/s10600-010-9561-1
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids of Cortusa turkestanica seed oil

Abstract: 547.915 A. M. Nigmatullaev, and A. I. GlushenkovaThe composition of free and bound lipids from seeds of Cortusa turkestanica A. Lozinsk (Primulaceae) was studied. The fatty acid composition of principal acyl-containing classes was established using GC/MS. It was found that triacylglycerines isolated from free and bound lipids contained the usual acids and rarely encountered polyunsaturated 18:3 Z-6 (J-linolenic, 8.8 and 3.2%) and 18:4 Z-3 (stearidonic, 0.7 and 0.4%) acids and were enriched in linoleic acid (18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The results showed that the samples were rich in lipids and lipophilic compounds, which were observed previously in the starting material [5,6]. Their qualitative composition including neutral lipids (NL), glycolipids (GL), and phospholipids (PL) in addition to carotinoids and chlorophyll pigments also turned out to be identical.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…The results showed that the samples were rich in lipids and lipophilic compounds, which were observed previously in the starting material [5,6]. Their qualitative composition including neutral lipids (NL), glycolipids (GL), and phospholipids (PL) in addition to carotinoids and chlorophyll pigments also turned out to be identical.…”
supporting
confidence: 60%
“…Waste samples were obtained from the pilot plant of the Yunusov Institute of the Chemistry of Plant Substances, AS, RU. Lipids from reprocessed raw material of these plants were previously studied [5,6].The wastes were a dark-green resinous mass with a brown tint and herbaceous aroma. Preliminary analyses for the presence of lipids were carried out by common TLC methods on Silufol plates and plates with thin layers of silica gel [7] using comparison with authentic samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation